Faces from the front: Harold Gillies, the Queen’s Hospital, Sidcup and the origins of modern plastic surgery - Andrew Bamji (Scientia Militaria, 2022)
Faces from the front is not a fresh title recently hitting the shelves. The publication originally appeared in late 2017 with a reprint appearing earlier this year. The deceitfully ‘thin-looking’ publication contains unbounded treasures, which could be attributed to the author’s passion for the subject clearly shining through. Andrew Bamji is not your average journalist or hobby writer turned amateur historian, but a physician in rheumatology by training, a published author, and a consultant archivist and researcher. In writing the book, Bamji drew from an estimated 2 500 case files, personal communication with a variety of individuals, and secondary literature. Given the depth of research, it is hardly surprising that the book has received much praise since its initial appearance and even won some awards, including the prestigious British Medical Association Medical Book Awards category ‘Basis of medicine’ in 2018.599 However, is such significant acclaim warranted, especially from a historian’s perspective? All too often some popular history writer makes it to some best seller or must-read list but is riddled with over-exaggeration, over-simplification or inaccuracies.